Repatriation, Incorporation and Destruction: the destination of the Caster Collection at the Museu Nacional/UFRJ, Brazil (Terr@ Plural, 2021)
In the mid-twentieth century, geologist Kenneth E. Caster collected fossils of South American Paleozoic and Mesozoic invertebrates, further contributing to important research for Brazilian geology. The collected paleontological collection was later taken to study at the University of Cincinnati (USA), where it remained for more than six decades. In 2016, in an unprecedented agreement between the Universidade de Cincinnati and the Museu Nacional/UFRJ, the Caster collection was repatriated, incorporating it into the collection of paleoinvertebrates of the Museu Nacional/UFRJ. The report clarifying the trajectory of the collection's repatriation and its tragic, but partial, destruction in the institution's fire in 2018 and its current destination is the objective of this paper.
Keywords: Paleontological heritage; Fossils; Paleoinvertebrates